Pengaruh pemberian ekstrak kedelai hitam (Glycine soja.) berbagai dosis terhadap kadar glukosa darah, kadar insulin, dan HOMA-IR - Kurniawati, Dewi M; Dharmana, Edi; Rachmawati, Banundari; Pemayun, Tjokorda Gde Dalem (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2017)
Background: Obese is risk factor for abnormal glucose homeostasis and causes oxidative stress that can decrease insulin sensitivity resulting in hyperglycemia and hyperinsulinemia. Black soy bean contains anthocyanins and isoflavones, it is expected to reduce oxidative stress. Objective: Determine the effect of various dosage of black soybean extract (Glycine soja.) on blood glucose, insulin levels, and HOMA - IR in obese Sprague Dawley (SD) rats.Methods: True experimental study with randomized controlled pre test-post test design in male SD rats. Twenty four samples divided into 4 groups: control (K), 500 (P1), 750 (P2), and 1000 mg/kgBW (P3). Rats were induced to become obese with High Fat Sucrose Diet (HFSD) for 4 weeks then black soybean extracts were given for 2 weeks..Results: There was no difference in blood glucose before and after treatment (p> 0.05). There were differences on insulin levels in 500 (p = 0.012) and 750mg/kgBW (p = 0.020) doseges. There were differences on HOMA-IR in 500 (p = 0.043) and 750mg/kgBW (p = 0.028) dosages. There was difference in insulin levels’s difference (p = 0.009) between groups.Conclusion: There are differences on insulin levels and HOMA – IR in 500 and 750 mg/kgBW dosages groups. However, there is no difference on blood glucose before and after black soybean extract treatment. The most decreased levels of blood glucose, insulin and HOMA- IR were in 750mg/kgBW dosage.